ENGAGING ADULT DAY SERVICE SITES IN THE ADS PLUS PRAGMATIC TRIAL. (11th November 2018) - Mitchell, L; McCarron, H; Weinstein, A; Gaugler, J E
Abstract: In this presentation, we discuss the process of engaging with the adult day service programs involved in the ADS Plus study. These programs included 15 intervention sites, 15 control sites, and 22 sites that were not randomized to either the control or intervention group but remained involved as advisory "initiative" sites. The process of engagement included recruitment of sites, collection of basic information to determine eligibility, randomization, completion of reliance agreements, orientation, training of interventionists, and continued contact through the course of the study. In this session, members of the research team describe each stage of the engagement process, and discuss effective strategies for engaging with interventionists and other site staff members in support of the ADS Plus study. Unanticipated challenges, such as complications with training, staffing changes, recruitment and enrollment, are also discussed, along with problem-solving strategies for addressing such concerns.